Feeding diet containing concentrate with fermented Arenga pinnata by-product on nutrient intakes, digestibility, and milk quality of lactating dairy cows - Sulistyowati, E.; Wiryawan, I. K. G.; Badarina, I.; Naibaho, S. H.; Apreza; Pratama, W. A.; Cahyadi, C.; Sistanto; Waspodo, R. J. (International Journal of Agricultural Technology, 2025)
Utilizing fermented Arenga pinnata, a product produced by Pleurotus ostreatus that was transferred for 5 weeks until the full hyphae were grown, as an alternative feedstuff. This biomass was ready to be used as one of the ingredients in substitution with rice bran in the concentrate. They were concentrated with fermented Arenga (CFA) by-products, specifically CFA0 (0/35), CFA10 (10/25), CFA15 (15/20), and CFA20 (20/15). In comparison, other ingredients were ground corn, soybean meal, palm oil, mineral mix, Curcuma xanthorrhiza, yeast, NaCl, CaCO3, and TSP (Triple Superphosphate). Those were all in the same amount, totalling 65%. The results showed that the crude protein content of fermented A. pinnata was improved by 11.62%, compared to 1.55% in non-fermented A. pinnata. Its crude fibre content decreased from 30.18% to 24.31%, respectively, in non-fermented and fermented A. pinnata. Meanwhile, the contents of NDF, ADF, hemicellulose, and cellulose were reduced with increased levels of fermented A. pinnata by-product in rice bran. On the other hand, Ca, P, and Ca/P (2.04) were found to be high in CFA20. Feces production (19.50 kg/d on average) was not different (P>0.05) among the three diets containing fermented A. pinnata by-product concentrates in lactating dairy cows. The nutrient contents in feces were not differed (P>0.05) among these diets, except for ether extract (P<0.05), which was shown to be higher in CFA15 and CFA20. All nutrient intakes were very significantly (P<0.01) decreased with increased the fermented A. pinnata by-product in concentrates. Digestibility of nutrients was not differed substantially (P > 0.05), while ether extract was significantly decreased (P < 0.05) in CFA15 (86.57%) and CFA20 (87.51%), compared to a diet without fermentation. A. pinnata in the concentrate. Milk yielded (8.52 kg/d in FCA0 and 8.31 kg/d in CFA20 diets) and milk composition were not significantly affected (P > 0.05). These results indicated that incorporating up to 20% fermented A. pinnata into the concentrate, replacing rice bran found to be a suitable option for lactating dairy cows’ diets.